Characteristics and Main Controlling Factors of Fractures within Highly-Evolved Marine Shale Reservoir in Strong Deformation Zone - Zhou, Xuehui; Wang, Ruyue; Du, Zhili; Wu, Jing; Wu, Zhonghu; Ding, Wenlong; Li, Ang; Xiao, Zikang; Cui, Zixian; Wang, Xinghua (Frontiers in Earth Science, 2022)
Based on the systematical observations of cores, thin sections, and scanning electron microscope (SEM) sections, together with the testing data and characteristic parameters, this paper discussed the characteristics, controlling factors of fractures, and its control on shale gas accumulation, in the Lower Cambrian Niutitang Formation black shale reservoir of Well YX1 in the northern Guizhou Province. The results show that macro structural fractures are common in the Niutitang Formation, which can be divided into shear fractures (e.g., high dip-angle shear fractures and low dip-angle slip fractures), tensional fractures, and tension-shear fractures. Non-structural fractures in microfractures can be divided into organic-related fractures and inorganic mineral-related fractures. Most of the structural fractures were filled, and the types of fillings are diverse. The staggered relationships of fractures confirm the complexity of tectonic movement in the study area. The formation of structural fractures in Well YX1 is mainly controlled by the major fault. The influence of mineral composition and content, mechanical properties and brittleness, and organic matter content of rocks on the characteristics of the fractures are external manifestation of sedimentary environment. Affected by diagenetic evolution, organic matter-related fractures are not common. Compared with other shale gas reservoirs in China and abroad, the organic-rich shale reservoir of Well YX1 is characterized by both “geological sweet spots” and “engineering sweet spots”; however, strong deformation and faulting led to the loss of shale gas and damage of overpressure environment. Therefore, it is suggested that small-scale fractures caused by tectonic movements but without large penetrating faults are the most favorable for shale gas reservoirs. Based on the complicated tectonic setting in northern Guizhou, the formation pressure should be taken into account.